The Notary Authorities to Act as an Waqf Pledge Deed Official (PPAIW) Based on the Waqf Law - Gloria Gita Putri Ginting; Aulia Aulia; Dilla Aningrum (CV. Ridwan Publisher, 2023)
Waqf as one of the legal acts that has long lived and implemented in society, whose arrangements are incomplete and are still scattered in various laws and regulations. The role of the Notary in the waqf legal actions that have been running so far is related to the ratification of the nazhir legal entity. This study aims to determine the implementation of the making of the Waqf Pledge Deed carried out by a Notary who acts as the Official for Making Waqf Pledges (PPAIW), and to find out the Authority of a Notary to act as the Official for Making Waqf Pledges (PPAIW). This research is a descriptive research. Descriptive research aims to accurately describe the characteristics of an individual, condition, symptom or certain group, or to determine the spread of a symptom, or to determine whether there is a relationship between symptoms and other symptoms in society. Implementation of making the Deed of Waqf Pledge carried out by a Notary as PPAIW which is as stated in the explanation of the provisions of the Law on Notary Position Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position.